SOSIALISASI POS PEMBINAAN TERPADU TERHADAP PENYAKIT TIDAK MENULAR PADA INSTITUSI DI SEKOLAH DASAR IT CENDEKIA ANDALAS KOTA PADANG - Suci Maisyarah Nasution; Siti Nurhasanah; Hamidatul Yuni (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
COVID-19 cases in Indonesia began to be reported positive confirmed on March 2, 2020, with 2 cases. In West Sumatra Province, 182 positive cases of COVID-19 have been confirmed, starting on May 2, 2020. During the current pandemic, visits to health services have begun to decrease to fear making visits in crowds. Teachers and employees are required to be pillars of health for students and their parents; problems to control health regularly must also be presented in the school environment. So that all teachers and employees are always healthy and productive in carrying out their activities. This community service aims to periodically control the health of teachers and employees through socialization and introduction of Posbindu and regular health checks in the form of Posbindu (Integrated Guidance Post) PTM (Non-Communicable Diseases) Institutions. Community service is carried out at SD IT Cendekia Andalas. The targets of this service are teachers and school employees; the approach method is carried out by socializing, discussing, and forming cadres, distributing Posbindu equipment for further training in the future, and achieving the objectives of implementing Posbindu. Most of the community service participants in general still do not know about the Institutional PTM Posbindu; it is recommended that further form a team of Posbindu cadres as a program driving team; it is hoped that all teachers and employees at SD IT Cendekia Andalas will be exposed to the importance of regular health checks through the Institutional PTM Posbindu, health teachers and employees are monitored safely, and the spread of Covid-19 in crowds can be avoided.